Perbedaan Hasil Belajar Kognitif Geometri menggunakan Media ICT dengan Program Adobe Flash CS6 Berbasis STAD di Kelas V SDN 01 dan 09 Bandar Buat - Ningsih, Haryati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of  the research is to know differences in cognitive learning outcomes of students from the use of ICT media adobe flash CS6 program at SDN 01 and 09 Bandar Buat. The method used in this research is experiment. This type of research is a quasy design experiment in the form of nonequivalent control group design. The sampling technique is purporsive sampling. Sample class is class V SDN 01 Bandar Buat. The instrument used in this study is an objective test with multiple choice types. Data analysis technique is inferential statistical test with t-test. Based on the results of the study obtained the average value of experimental class 82.66 and control class 74.84. Hypothesis test results using the t-test on the real level α = 0.05 obtained t count = 2.36 and t table = 1.99 so that t count> table the H1 hypothesis in this study is accepted and rejected Ho, namely there are significant differences from the use of ICT media programs Adobe Flash CS6 on cognitive learning outcomes identifies the properties of building space in class V SDN 01 Bandar Buat. Keywords: ICT, Adobe Flash CS6, STAD, Learning Outcomes.